2010
DOI: 10.1021/je901050v
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical Properties of 1-Propyronitrile-3-alkylimidazolium Bromide Ionic Liquids at Temperatures from (293.15 to 353.15) K

Abstract: In the present work, a series of 1-propyronitrile-3-alkylimidazolium bromide ionic liquids ([C 2 CN C n im]Br, where n ) 4, 6, 8, and 10) were synthesized and characterized using Fourier transform infrared spectroscopy (FTIR), NMR, and elemental analysis. Physical properties such as density, viscosity, and refractive index are measured and reported for a temperature range of (293.15 to 353.15) K and at atmospheric pressure. The influence of the alkyl chain on these properties is discussed. The present synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
121
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(139 citation statements)
references
References 34 publications
16
121
0
Order By: Relevance
“…The obtained values are in reasonable agreement with the expected ones estimated by summing the cholinium cation (93.1 cm 3 ·mol -1 ) 48 and the AA molar volumes 58 measured in solution by 65 other authors. Our experimental data were higher of less than 12%, which is reasonably because the excluded volume was not considered in the calculation.…”
Section: Density Measurementssupporting
confidence: 90%
See 2 more Smart Citations
“…The obtained values are in reasonable agreement with the expected ones estimated by summing the cholinium cation (93.1 cm 3 ·mol -1 ) 48 and the AA molar volumes 58 measured in solution by 65 other authors. Our experimental data were higher of less than 12%, which is reasonably because the excluded volume was not considered in the calculation.…”
Section: Density Measurementssupporting
confidence: 90%
“…44 50 sulfur atom should not be much greater than about 20 % with respect to that of a methylene group while the molecular weight of sulfur is about 128 % higher than that of a methylene group, 46 the presence of sulfur could give an important contribution to the overall density of the ILs. Using the values of the van der Waals 55 volume of free amino acids in solutions, 4748 65 with respect to that formed by the classical hydroxyl group, 25 does not seem to give a significant contribution to the density values. It is worthwhile to compare our densities with those obtained for other AA based ILs.…”
Section: Density Measurementsmentioning
confidence: 98%
See 1 more Smart Citation
“…The instrument was calibrated with Millipore-grade water using ILs with data previously established by our research group [12][13][14]. The viscosities and densities of the ILs were measured in the temperature range of 293.15-373.15 K with ±0.01 K accuracy and uncertainties of 0.5 % and ±5 9 10 -4 gÁcm -3 , respectively.…”
Section: Viscosity and Densitymentioning
confidence: 99%
“…Results showed that incorporation of more alkyl groups or increasing the length of the alkyl group chain on the imidazolium cation caused increases in the refractive index, which may be due to increases in electron density on the alkyl group. Increases in electron density have been suggested to increase the refractive indices of ILs [12]. 4 ].…”
Section: Refractive Indexmentioning
confidence: 99%